ANATOMICAL BASIS OF INGUINAL HERNIAS IN CHILDREN AND ITS MANAGEMENT IN THE GENERAL SURGICAL PRACTICE - Dr. Zahida Akhter; Dr. Aijaz A Rather; Dr. Showket Majeed; Dr. Sajad Hamid (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUND: Inguino-scrotal swellings are a common incidence in pediatric age groups, often associated with abnormalities inside the descent of the testis and the failure of the processus vaginalis to shut well. Amongst those anomalies, inguinal hernia and hydrocele are the maximum often determined congenital situations. The occurrence of inguinal hernia is mainly high in preterm toddlers. With advancements in infertility treatment and upgrades in neonatal care, the survival charge of untimely toddlers has increased, circuitously leading to a better incidence of inguinal hernia and hydrocele inside the pediatric population.Diagnosis of inguinal hernia in pediatric patients is based totally at the records supplied with the aid of mother and father and medical examination performed by means of pediatricians and  surgeons. Extra investigations are carried out to rule out any related anomalies. As soon as the prognosis is confirmed, the most common remedy for inguinal hernia in pediatric patients is surgical closure of the patent processus vaginalis, known as inguinal herniotomy. whilst laparoscopic restore is a well-set up remedy choice for inguinal hernia in adults, its position in pediatric instances is restrained. A few surgeons may also choose laparoscopic restore, mainly in bilateral instances. This look at ambitions to discover the connection among various factors consisting of age, sex  and maturity, and the prevalence of inguinal hernia in children.OBJECTIVES: To study the epidemiology, management and outcome of inguinal hernia in children. Additionally, it seeks to identify any associated anomalies and evaluate the consequences of surgical intervention in pediatric sufferers with inguinal hernia at our Tertiary care center METHODS: A prospective study was conducted on pediatric patients with inguinal hernia for a period of 18 months, between 2021 to JAN 2024. Patients from newborn to 13 years of age were selected for this study.  RESULTS: Inguinal hernia can occur at any age, but the majority of patients are seen between 1 to 5 years of age. It is more commonly seen in male children and incidence is slightly higher on right side. Almost all of the inguinal hernia in the pediatric age group is of indirect type, which develops due to congenitally patent processus vaginalis.CONCLUSION: Early surgical intervention in form of Inguinal herniotomy is the most appropriate management of inguinal hernia in children.